CHALLENGE IN TREATING OPTIC NEURITIS IN PATIENT WITH CEREBRAL TOXOPLASMOSIS RELATED TO IMMUNOCOMPROMISED CONDITION - Latifah, Latifah; Vierla, Wino Vrieda (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2024)
Introduction: This study aimed to discuss the prognosis of optic neuritis in a patient with cerebral toxoplasmosis related to an immunocompromised condition. Case Report: A 28-year-old female complained of blurred vision and double vision 2 weeks before admission, accompanied by headache, low extremities weakness, dysphonia, and dysphagia. Visual acuity of both eyes was 6/30 and worsened to 6/60 in a couple of days. Anterior segment examination revealed anisocoria pupil, and RAPD was positive in the left eye. Funduscopic examination showed a blurry margin and hyperemia of the optic nerve head. There was impaired eye movement, indicating oculomotor and abducens nerve palsies. High titer of IgG Antibody Toxoplasma (264) and very low titer of CD4 (<50) with non-reactive HIV rapid test were found in laboratory findings. Multiple ring enhancement was shown in MRI finding. Unfortunately, patient passed away during hospitalization due to respiratory failure. Discussion: Toxoplasmosis-associated optic neuritis is rare and usually becomes potentially serious. Although parasite detection by microscopy and bioassay is considered the gold standard for the diagnosis of toxoplasmosis, clinical diagnosis relies more on serological examination methods. The high proportion of deaths from this disease is mostly caused by late diagnosis of the infection. Conclusion: Optic neuritis that accompanied by systemic disorders needs special attention and comprehensive treatment among multidisciplinary divisions, especially in the immunocompromised condition. Early detection and primary prevention are important to improve prognosis and survival rate.